Supratentorial tumour surgery and anaesthesia [Supratentoriyal tümör cerrahisi ve anestezi] - (:unkn) unknown (My University, 2004)
Space-occupying lesions (such as tumour, abscess, hematoma) at the supratentorial area are the subjects that concern the neuroanaesthesiologists most. Approximately 36% of the primary tumours of brain and central nervous system are localized in this area. These tumours grow slowly, but they increase intracranial pressure by obstructing cerebrospinal fluid drainage and compressing peripheral veins. Compensating mechanism for intracranial pressure becomes insufficient as the volume of the tumour increases, and signs and symptoms of increased intracranial pressure such as headache, nausea, vomiting, papillae edema occur. Although tumours localized in the supratentorial area have different pathological characteristics, anaesthetic approach to the patients with these tumours is similar; and aim the maintenance of hemodynamic stability, comfortable conditions for surgery, fast and smooth awakening.
Keywords: Anaesthesia; Craniotomy; Supratentorial tumour